Measures of JSC “Uzbekneftegaz” contributing to sustainable development (Eurasian Research Bulletin, 2023)
Thanks to the implementation of the program, Uzbekistan managed not only to ensure its energy independence, but also to strengthen its gold and foreign exchange reserves. For example, in 2008, at the expense of its own funds, as well as funds from the Fund for Reconstruction and Development of Uzbekistan, JSC «Uzbekneftegaz» mastered more than 1.860 trillion. Sum of capital investments. The growth rate of natural gas production amounted to 103.7%. One of the principles of the new water legislation is the priority of the protection of water bodies over their use, in which there should be no negative impact on the environment. Oil and gas industry facilities are mainly located in regions with limited water resources. Therefore, their rational use can rightly be attributed to one of the largest environmental problems. Data analysis showed that in recent years, oil and gas industry facilities have carried out oil and gas operations in accordance with the legislation of the Republic of Uzbekistan in compliance with generally accepted standards in the international oil and gas industry